HUBUNGAN KADAR HEMOGLOBIN, PERSENTASE LEMAK TUBUH, AKTIVITAS FISIK DAN STATUS MEROKOK DENGAN DAYA TAHAN AEROBIK ATLET SOFTBALL (Studi di UKM Softball Universitas Diponegoro) - Anna Herdina; M. Zen Rahfiluddin; Apoina Kartini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Achievements of softball that having ups and downs were a concern for athletes in Indonesia, as evidenced by the 2015 Sea Games and the 2018 Asian Games which did not contribute to the gold medal due to lack of attention to athlete's health. Softball athletes are required to pay attention to hemoglobin levels, body fat percentage, physical activity, and smoking status because that are strongly related to an athlete's aerobic endurance so as to improve performance when tournaments. The purpose of this study was to analyze the relationship between hemoglobin levels, body fat percentage, physical activity, and smoking status with aerobic endurance of softball athletes. This research is an explanatory research with cross sectional design. Sampling using a purposive sampling technique with a sample of 30 athletes. Data were collected using the interview method, hemoglobin levels by the cyanmethemoglobin method, body fat percentage using BIA, physical activity using recall and aerobic endurance using the Multistage Fitness Test method. Data in this study were analyzed using Rank Spearman. The results of univariate analysis showed that most respondents had normal hemoglobin levels, percentage of body fat including obesity, physical activity including moderate, smoking status including mild smokers, and aerobic endurance in the mild and moderate category. The results of the bivariate analysis showed that there was a relationship between hemoglobin levels (p=0,011;r=0,458), percentage of body fat (p=0,000;r=−0,742) and physical activity (p=0,000;r=0,942) with aerobic endurance, as well as not related to the relationship between smoking status with aerobic endurance (p = 0.725;r=−0,067). Softball group managers and athletes are advised to do physical exercise and pay attention to nutrient intake.